Transcriptional Regulation of Iron Distribution in Seeds: A Perspective - Roschzttardtz, Hannetz; Gaymard, Frederic; Dubos, Christian (Frontiers in Plant Science, 2020)
Several transcription factors have been involved in the regulation of gene expression during seed development. Nutritional reserves, including iron, are principally accumulated during seed maturation stages. Using the model plant Arabidopsis thaliana, it has been shown that iron is stored during seed development in vacuoles of the endodermis cell layer. During seed germination, these iron reserves are remobilized and used by the seedling during the heterotrophic to autotrophic metabolism switch. To date, no information about how iron distribution is genetically regulated has been reported.